O triste olhar em frente ao espelho: uma análise sobre a mulher e a afetividade negra em The Bluest Eye de Toni Morrison - Passos, Karla Cristina dos (Universidade Federal de São Carlos, 2019)
The present study sets out to examine the book The Bluest Eye (1970), a novel authored by Toni Morrison focusing on the theme regarding affectivity and black women recited in the narrative. For such, we employ a theoretical-critical perspective that allows us to bring together the work to the period’s social and historical context of publication as well as the 1940s, a period in which the narrative undergoes. We analyzed through a dialectical manner the work’s form and content, intending to heighten the discussions associated to women and black affection expressed in the novel. To that end, we cast the reflections of theorists who debate the relationship concerning literature and society like Antônio Candido, Roberto Schwarz and Fredric Jameson. We will employ, as a thematic field, the memories of characters such as Claudia McTeer, Pauline Breedlove and Cholly Breedlove, as well as some of the work’s autobiographical features. The character Claudia will be emphasized for being the very narrator of the novel and her questions sanction us to access the perspectives of life handed out to black girls and women in the narrative. Claudia is also recited as the author's voice throughout the text, vindicated by the novel’s scenery and a statement by the author concerning her inspirations. The Breedlove’s analysis is established through an inner focus on their childhood and adolescence flashbacks regarding origins and traumas. It is through the narrator and the focal intensification we seek to entree the author's utopian impulse to render the subordinate position of these women in the United States of the 1940s, their social and family status, the violence and financial lacking, also from rights and affection in which they were downcast.
The sad look in front of the mirror: an analysis concerning black women and the affectivity in The Bluest Eye by Toni Morrison
Keywords: Literatura e sociedade; Afetividade negra; Toni Morrison; Black women; Black affectivity; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS